2005
DOI: 10.1002/j.2162-6057.2005.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational Intervention and the Development of Young Art Students' Talent and Creativity

Abstract: This study focuses on behavior associated with young art students' developing artistic talent (skills and art‐making behavior) and creativity (personal expressions of visual information). The study examines the role of personal expertise in a student's development of problem finding, domain‐specific technical skill, perseverance, evaluation, and creative ideation. The study compares 30 experienced art students' artistic processing and products with those of 29 novice art students. Both groups are 7‐ through 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…The research on how children grow and learn in the areas of aesthetic perception and artistic production does not provide a clear picture of how these abilities develop or what promotes them (see, for example, Beattie, 2000;Rostan, 2005). Part of the difficulty is that there is not strong agreement on what should be assessed or how that assessment should take place.…”
mentioning
confidence: 99%
“…The research on how children grow and learn in the areas of aesthetic perception and artistic production does not provide a clear picture of how these abilities develop or what promotes them (see, for example, Beattie, 2000;Rostan, 2005). Part of the difficulty is that there is not strong agreement on what should be assessed or how that assessment should take place.…”
mentioning
confidence: 99%
“…Whereas some (Chen et al, 2005;Chen, Himsel, Kasof, Greenberger, & Dmitrieva, 2006) argue for a domain-general characteristic, others believe creativity to be domain relevant (Dow & Mayer, 2004;Kaufman & Baer, 2004;Rostan, 1998;Runco & Nemiro, 2003;Sternberg, 2006a;Sternberg & Lubart, 1995) and possibly even task specific within a domain (Baer, 1998(Baer, , 2003Rostan, 2005). Even in very young children, creative performance in one domain was quite independent of creative performance in another, and in some instances, there was even a negative relationship (Han, 2003).…”
mentioning
confidence: 99%
“…In her results, Rostan (1998Rostan ( , 2005) mentioned children could discuss criteria to identify good artists. The criteria for good artists are motivation, knowledge about art, how to use materials.…”
Section: Artistic and Creative Identitymentioning
confidence: 99%
“…In addition the acquisition of skills was very important for all ages 8-10 year olds because they were interested in learning how to be better artists (Rostan, 1998). Rostan (1998Rostan ( , 2005 suggested that by comparing the young artist's definition of artistic identity with adults and adolescents, her conclusion was that young artists have a very sophisticated definition of creative and artistic identity. In her interviews she noted that the children participated in art criticism.…”
Section: Artistic and Creative Identitymentioning
confidence: 99%
See 1 more Smart Citation